Innocent Until Proven Guilty: Addressing Problem of Criminal Investigation in Pakistan - Ghani, Abdul; Ayub, Zainal Amin; Mat Rus, Mukhriz (Vytautas Magnus University, 2022)
Criminal investigation of murder cases in Punjab, Pakistan is not up to mark, and this results in pendency of such cases for years. The time span for data collection for the present study ranges from January 01 to 31st of December 2020. The data is delimited to the murder cases filed in district Multan, Punjab (Pakistan)during the mentioned span of time. The data has been analyzed by using analytical research methodology techniques. Some of the filed cases out of ninety-five (95) have been analyzed in detail, while the rest of the murder cases filed in district Multan, have been generalized to support qualitative findings quantitatively. These cases were submitted in-district courts of Multan for justice. The analysis of the collected data so far reveals that none of the filed cases (95) has been decided. Rather, five cases out total have yet not been submitted to the courts after investigation by the police concerned. Rest of cases are being trailed in the session courts at initial stages. It contends that the rate of dispensation of criminal cases is alarmingly low in the mentioned law courts of Multan, Punjab (Pakistan). The studies recommend that an advanced system police investigation must be introduced, investigation officer should be scientifically trained, and the sense of professional and moral honesty should be imparted among them. In this way the police investigation system in Punjab, Pakistan can be improved according to the demands of modern time